Core-shell magnetic-plasmonic nanoparticles enclosed in a biocompatible dehydropeptide-based hydrogel containing lysine - Veloso, Sérgio Rafael Silva (2019)
The combination of magnetic nanoparticles and hydrogels affords magnetogels, improving the manipulation of physicochemical properties and widening the range of applications, such as magnetic resonance imaging, biosensing, hyperthermia, drug delivery and as a template material. The introduction of plasmonic properties will synergistically enhance anticancer therapeutic strategies on the desired target through photothermia, drug release and photodynamic therapy. In this work, superparamagnetic nanoparticles coated with a gold shell were successfully incorporated into a self-assembled peptide-based hydrogel linked to a naproxen group, a lysine residue to stabilize the gold nanoparticle surface, and a dehydroamino acid that provides protease resistance. The new magnetogel was evaluated as a drug nanocarrier and the photothermia potential of the nanosystem was assessed. The developed nanosystem exhibited promising results for photothermia application, though future combination with other hydrogels will be required to improve its applicability.